TPMT in the treatment of Crohn's disease with azathioprine. Issue 2 (1st August 2002) - Lennard, L
Abstract : Azathioprine induced profound myelosuppression linked to TPMT deficiency has now been documented in many patient groups, including those with Crohn's disease. At the start of azathioprine or mercaptopurine therapy, measurement of TPMT activity has a role in identifying the 1 in 300 patients who are at risk of severe myelosuppression when treated with standard thiopurine dosages. During the initial months of azathioprine therapy a knowledge of TPMT status warns of early bone marrow toxicity. In patients established on azathioprine these is no clear evidence to suggest that TPMT is predictive of clinical response or drug toxicity, indicating a role for TPMT in the prediction of early events rather than long term control. In patients with Crohn's disease on long term azathioprine therapy, it is clear that myelosuppression, particularly leucopenia, is caused by other factors in addition to variable TPMT activity and therefore monitoring of blood cell counts throughout treatment is essential.